DEGRADASI LAHAN AKIBAT BERBAGAI JENIS PENGGUNAAN LAHAN DI KABUPATEN DHARMASRAYA - Syafrimen Yasin (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2004)
Intensive deforestration for the purpose of agricultural field and transmigration area has happened lately in Dharmasraya Regency, West Sumatra. Land use change from forest into dry land farming, mixed trees and oil palm plantation, as well as rubber plantation has caused different level of soil fertility as a consequence of ecology changes of the areas. The objectives of this research were to identify the change of soil organic matter content, plant nutrition level, as well as bulk density of the soils at each land use. This research was conducted in Sungai Rumbai, Dharmasraya Regency in 2007. Soil samples were taken from 5 land use, those were dryland farming, mixed trees, oil palm plantation, rubber plantation, and natural forest. The soil samples, then, were analysed for the soil organic matter content (%), N-, P-, and K-content, as well as bulk density (BV) in soil laboratory, Agricultural Faculty, Andalas University Padang. The result showed that land use change from forest ecosystem into other ecosystems had decreased soil fertility level. This was reflected by the decreasing soil organic matter content, increasing soil bulk density. Nutrient status of the soil also decreased, especially potassium (K) level. Compared to the forest ecosystem, soil organic matter decreased by 13, 26, 33, and 36% respectively for dry land farming, mixed trees and oil palm plantation, as well as rubber plantation. Soil bulk density of the land use which was still close to soil under forest ecosystem (0.83 gcm-3) was found in rubber plantation (1.00 gcm-3), then followed by mixed trees (1.11 gcm-3). Potassium level of the land uses which were close to forest ecosystem (0.44 me/100g) was in rubber plantation (0,33 me/100 g), as well as in oil palm plantation(0,34 me/100 g). Based on the results above, it can be concluded that rubber and oil palm plantation was types of land use having better soil ecology compared to the other land use. Kata Kunci: Degradasi Lahan, Ekosistem Hutan, Penggunaan Lahan